Protocol for a randomized controlled trial of electroacupuncture in the management of patients with axial spondyloarthritis in Singapore (E‐AcuSpA). Issue 2 (28th December 2021) - Fong, Warren; Kwan, Yu Heng; Quek, Su‐An; Lim, Ader; Wong, Chiah Yuen; Chua, Shin Yoong; Tan, Hui Chin; Eng, Clara; Tan, Choy Tip; Dong, Bao Qiang; Huang, Youyi; Tan, Chuen Seng; et al.
Abstract: Background: Despite therapeutic advances, treatment of patients with axial spondyloarthritis (axSpA) continue to pose as a challenge as many do not respond well to conventional Western medications, such as nonsteroidal anti‐inflammatory drugs (NSAIDs) and biologic disease‐modifying antirheumatic drugs (bDMARDs). Hence, acupuncture is a possible alternative. Some studies found electroacupuncture to be better than manual acupuncture, though no trials have been conducted in patients with axSpA. This clinical trial aims to evaluate the clinical efficacy, safety, and cost‐effectiveness of electroacupuncture compared to manual acupuncture for patients with axSpA. Methods/Design: This randomized controlled trial will recruit 100 patients diagnosed with axSpA, who have active disease despite NSAIDs and bDMARDs. Eligible patients will be randomized to receive either electroacupuncture or manual acupuncture in a 1:1 ratio. All participants will receive standard rheumatologic care in addition to 20 acupuncture sessions. The mean difference in Bath Ankylosing Spondylitis Disease Activity Index score between the 2 groups over 12 weeks will serve as the primary outcome. Secondary outcomes include improvements in other clinical, quality of life, and economic outcomes over 24 weeks. All adverse events will be recorded. Discussion: Results from this trial may provide evidence regarding the clinical effectiveness, safety, and cost‐effectiveness of electroacupuncture compared to manual acupuncture for patients with axSpA, and guide implementation into clinical practice. Limitations of this trial include the lack of patient blinding, use of a repeated measures design, and possible variation in acupuncture technique amongst the various Traditional Chinese Medicine practitioners. Highlights: There are currently a lack of randomised controlled trials comparing the efficacy between manual acupuncture and electroacupuncture. This is a protocol for a randomised controlled trial comparing the efficacy between manual and electroacupuncture in patients with axial spondyloarthritis with inadequate response to conventional western medications. The mean difference in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score between the two groups over 12 weeks will serve as the primary outcome. Abstract : Graphical abstract of a randomized controlled trial comparing the efficacy of manual acupuncture and electroacupuncture for patients with axial spondyloarthritis. Primary outcome will be the mean difference in Bath Ankylosing Spondylitis Disease Activity (BASDAI) score over 12 weeks. Secondary outcomes will include improvements in other clinical, quality of life and economic outcomes over 24 weeks.